Thrombolytic and Anticoagulant Therapy for Pulmonary Embolism with High and Intermendiate Risk of Early Death. Part 3. An Effect on Pulmonary Perfusion with High and Intermediate Risk of Early Death - O. V. Nikitina; I. P. Mikhailov; N. Y. Kudryashova; E. V. Migunova; A. G. Dorfman; V. I. Avfukov (Неотложная медицинская помощь)
Background The advantage of thrombolytic therapy (TLT) over anticoagulant therapy(ACT) in patients with a high risk of early death (hemodynamic disorders) in acute pulmonary embolism is considered proven. But the advantage of thrombolytic therapy over anticoagulant therapy remains uncertain in patients with an intermediate risk. Perfusion lung scintigraphy helps provide a quantitative comparison of changes in pulmonary blood flow with the use of different treatment methods in subgroups of high and intermediate risk of an adverse outcome.The aim of study is to compare the effectiveness of thrombolytic and anticoagulant therapy in the treatment of acute pulmonary embolism in patients with a high and intermediate risk of early death in terms of the dynamics of pulmonary perfusion disorders.Study design: a prospective non-randomized study. The introduction of a thrombolytic was cosidered as intervention. The comparison group consisted of patients who received an anticoagulant. Thrombolysis in patients with intermediate risk was indicated in the absence of a potential threat of hemorrhagic complications, a deficit of pulmonary perfusion above 40%, a high level of pulmonary hypertension and a high probability of cardiac decompensation. The method of comparison was the quantitative result of pulmonary perfusion deficiency.Description of the method Radionuclide and CT studies were carried out using a hybrid system SPECT/CT Discovery NM/CT 670 (GE, USA): the perfusion was evaluated with 80–120 MBq of 99mTc macrotech radiopharmaceutical (RP) (effective equivalent dose of 0.8–1.3 mSv), CT angiography was performed with 70–100 ml of radiopaque substance Visipaque (effective equivalent dose of irradiation 9.4–10.3 mSv). The accumulation deficit of an area equal to a segment was counted as a perfusion deficiency of 5% (subsegmental 2.5%), inferior lobe — 25%, an area equal to the right lung — 55%, the left lung — 45%.Characteristics of the sample In a sample of 503 patients who received treatment at the Intensive Care Unit for Surgical Patients of the N.V. Sklifosovsky Institute for Emergency Medicine from 2011 to 2016, the overall mortality rate was 14.7% (95% CI 11.7; 18.1) (74/503); anticoagulation therapy — 17.8% (95% CI 13.5; 22.8) (50/281); thrombolytic therapy — 10.8% (95% CI 7.1; 15.6) (24/222); p=0.031, Fisher’s test, P=0.60. At a high risk of death, the mortality rate in the thrombolytic therapy group was 30.2% (19/63) versus 47.1% (32/68) in the anticoagulant therapy group; p=0.051, the Fisher’s test; P=0.51. At an intermediate risk, it was 3.2% (5/158) and 8.4% (8/214); p=0.049, the Fisher’s test, P=0.54. Changes in pulmonary perfusion deficiency as a result of treatment were performed in 169 patients who promptly underwent a primary and repeated dynamic scintigraphic study: 127 patients after thrombolysis (of which 38 patients had a high risk and 88 had an intermediate risk) and 42 patients who were treated with an anticoagulant (5 — high risk, 37 — intermediate risk). The groups did not differ in age and gender composition: the mean age was 59±16; Me 61 (49; 71) and 57±14 years; Me 58 (43; 67), respectively; p=0.50 (Mann–Whitney test); men/women: 50/77 and 12/30; p=0.27, the Fisher’s test. The groups differed in the presence of cancer: in the ACT group, the proportion of patients with cancer was 21.4% (9/42), and in the TLT group it was 4.7% (6/127), p=0.003, the Fisher’s test, P=0.85.Results Patients of high and intermediate risk, who received thrombolysis, were in a significantly more serious condition in terms of baseline characteristics. Both methods of treatment were effective. In high-risk patients, perfusion deficiency regressed: from 57±10% (Me 60 (50; 65)) to 31±15% (Me 30 (20; 40)), p<0.00001 (Wilcoxon test), Es=2.08, P=1.00 after TLT; from 38±9% (Me 40 (35; 40)) to 14±8% (Me 10 (10; 20)), p=0.043 (Wilcoxon test), Es=2.72, P=0.93 after ACT. In patients with intermediate risk, perfusion deficiency regressed: from 48±9% (Me 50 (40, 55)) to 24±13% (Me 20 (15; 30)), p<0.00001 (Wilcoxon test) after TLT; from 38±11% (Me 40 (30; 45)) to 24±15% (Me 15 (15; 30)), p=0.00003 (Wilcoxon test) after ACT. The effect size for TLT was Es=2.16, for ACT Es=1.13. The power of the study was P=1.00 and P=0.99.Conclusion Thrombolytic therapy was more effective in restoring pulmonary perfusion compared to anticoagulants in patients with an intermediate risk of early death: the effect of thrombolysis was greater than that of anticoagulant therapy (Es=2.16 and Es=1.13). The absence of the effect of restoring pulmonary perfusion during thrombolysis was noted less frequently compared to the results of anticoagulant therapy: in 5.5% (95% CI 2.2–11.0) vs. 19.0% (95% CI 8.6–34.1).